1999
DOI: 10.1089/end.1999.13.173
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Suprapubic Cystolithotripsy for Vesical Calculi in Children

Abstract: Extension of endourologic procedures to the lower tract reduces morbidity and hospital stay and thus the cost of treatment. Percutaneous suprapubic cystolithotripsy, in our experience, is a safe and cost-effective alternative to open surgery in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 14 publications
3
29
0
1
Order By: Relevance
“…High male to female ratio not exactly known but is similar to 5,7 other studies . Clinical presentations are similar to other 1 4 studies where vesiculolithissis was studied .…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…High male to female ratio not exactly known but is similar to 5,7 other studies . Clinical presentations are similar to other 1 4 studies where vesiculolithissis was studied .…”
Section: Discussionsupporting
confidence: 82%
“…However, urethral injury is a strong possibility in few instances specially in larger 5,12 stones . Similarly, in children, narrow caliber of the urethra 13 precludes the use of this procedure .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Boys are more commonly affected than in girls at a ratio of 8:1 [4], common age of occurrence is 2 -5 years. Our review concerning about giant bladder stones leading to renal insufficiency showed only three cases in children; all them were boys, mean age 9.66 years old, corresponding to 9.67% of the subjects reported.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%